Analisis Perbuatan Melawan Hukum dalam Sengketa Kepemilikan Tanah Akibat Tumpang Tindih Sertifikat Hak Milik, Study Putusan No. 12/G/2023 PTUN PBR - Fitra Fitra; Darmiwati Darmiwati; Bambang Sasmita Adi Putra (Journal of Innovative and Creativity (Joecy), 2026)
Land plays a strategic role in social, economic, and legal life, yet the certification system intended to guarantee legal certainty often fails in practice, as reflected in the persistent occurrence of overlapping land title certificates issued by land administration offices. This study examines Decision No. 12/G/2023/PTUN.PBR, in which three overlapping Sertifikat Hak Milik (SHM) were issued by the Pekanbaru Land Office, triggering a dispute over alleged detournement de pouvoir. The research aims to analyze the form of unlawful acts (perbuatan melawan hukum) in the issuance of overlapping certificates, examine the shifting judicial reasoning across the first-instance, appellate, and cassation levels, and formulate an appropriate model of legal accountability for the resulting material and immaterial losses. Using a normative juridical method with statutory and case approaches, the study relies on secondary legal materials analyzed qualitatively and deductively. The findings reveal that administrative negligence in verifying physical and juridical land data violated the principle of AUPB (asas kecermatan), fulfilling the elements of Article 1365 of the Civil Code, although the Supreme Court ultimately dismissed the case on absolute competence grounds. The study concludes that administrative remedies alone are insufficient to restore civil losses, recommending a clearer jurisdictional framework and a concrete compensation mechanism, alongside parallel civil litigation as an alternative recovery path.